Sistema de acompanhamento da saúde do idoso - MORAES, Samuel Furtado de (2019)
The growing technological advance is present in several areas of society, because, currently, the technology is necessary to be able to perform practically any routine task, being it in the business branch, private or hospital, for example. It is undeniable that with the insertion of technology and its administration made in the correct way can modify any organ in a positive way. However, for reasons such as lack of resources, knowledge or even lack of interest, some agencies do not exploit the potential of technology to improve their daily tasks, such as the Group of Education in the Elderly, located on campus of the Federal University of Pará in Castanhal PA. In view of this, this work aims to develop a Web system that complies with the need of this body, and can thus computerize the registration and monitoring of the elderly of this group.